2017
DOI: 10.32582/aa.58.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and overlap for 43 fishes in the North Aegean Sea, Greece

Abstract: This study presents the diet composition of 43 of some of the most abundant fish species from the North Aegean Sea, Greece. According to the diet analysis and fractional trophic level previously reported in the literature, 20 of the studied species were omnivores with a preference for animals and the other half were carnivores (15 with preference for fish and Cephalopoda, and seven with preference for fish and Decapoda), whereas Parablennius gattorugine was the only recorded omnivore with a preference for plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Qualitatively, the diet of the Adriatic pelagic fish species examined in this study was quite similar to those reported for the same species distributed in the Mediterranean area (small pelagics: Costalago et al, 2015;Mazlum et al, 2017;mediumsized pelagics: Rumolo et al, 2016;Karachle, 2017;Georgieva et al, 2019;Saglam and Yıldız, 2019). The slight differences in their relative proportions reported between studies likely reflect spatial and temporal variation in availability.…”
Section: Diet Composition By the Stomach Content Analysissupporting
confidence: 84%
“…Qualitatively, the diet of the Adriatic pelagic fish species examined in this study was quite similar to those reported for the same species distributed in the Mediterranean area (small pelagics: Costalago et al, 2015;Mazlum et al, 2017;mediumsized pelagics: Rumolo et al, 2016;Karachle, 2017;Georgieva et al, 2019;Saglam and Yıldız, 2019). The slight differences in their relative proportions reported between studies likely reflect spatial and temporal variation in availability.…”
Section: Diet Composition By the Stomach Content Analysissupporting
confidence: 84%
“…In coexisting species, various mechanisms useful to minimize competition for food resources, e.g. habitat separation, prey size, predator size and morphology, species segregation, differentiation in foraging tactics, have been reported (MacPherson 1979;Karachle 2017). Among these mechanisms, a differentiation in foraging tactics could partially explain the results obtained in this study and in Barría et al (2015).…”
Section: Trophic Niche Breadth and Trophic Niche Overlap Among Size Gmentioning
confidence: 99%
“…Unfortunately, most of the literature on trophic interactions, especially in the Mediterranean, usually focuses on the diet comparison of just two or three species (Valls et al 2011(Valls et al , 2017Barría et al 2015Barría et al , 2018. More complex studies are limited to a few papers, published in recent decades and focusing on the main predator groups, like bony fishes (Cabral et al 2002;Valls et al 2014b;Karachle 2017;Park et al 2017;Paul et al 2018), elasmobranchs (Orlov 1998;Valls et al 2011; Barría et al 2015Barría et al , 2018Kousteni et al 2018), cetaceans (Liu et al 2015) and cephalopods (Cherel et al 2009), while studies on betweentaxa interactions are even fewer (Valls et al 2014a(Valls et al , 2017. Concentration on large predator groups is driven by the predators roles in the food chain, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The few amphipods found in the stomachs should be considered as accidental prey, having been consumed along with the algae [39]. Meanwhile, juveniles of the piscivorous predator S. sphyraena [40,41] occurred only sporadically in the study area. Temporal variations of the diet were also observed in most of the fish species most probably due to the important factors of fish body size and prey availability in the marine environment [15,17].…”
Section: Discussionmentioning
confidence: 94%